Control and Navigation of Mobile Robots in Safety and Fire Protection - Juraj Uricek; Viera Poppeova; Vladimir Bulej; Jan Matik (Communications - Scientific letters of the University of Zilina, 2011)
This paper presents the actual situation of mobile robots (MRs) application in the field of safety and fire protection. At the beginning are described the basic structures and subsystems of each MR, reasons for their applications and some design examples of mobile robots applied for safety and fire protection. The second part of this paper presents several different conceptions of MR control systems with respect to dangerous applications. The last part of this paper is oriented on the methods of MR navigation and path planning. This part is related with maps and localization problem and describes why it is necessary to have a map in MR control system. There are presented some basic map types with their advantages and disadvantages.